A prática espacial cotidiana na cidade e a prática pedagógica no ensino de Geografia - Christan, Patrícia (2020)
The aim of this research is to analyse the daily spatial practices of Geography teachers and its relationship with the pedagogical practice in Basic Education. More specifically: to understand the everyday spatial practices as an important dimension of geographical teaching knowledge; to describe the perception of Geography teachers about their daily spatial practices in the city of Cuiabá; to characterise the pedagogical practice of teachers in the teaching of Geography, emphasizing the approach to the city of Cuiabá; to analyse the interface between the daily spatial practices and the pedagogical practice in Geography teaching. The methodological path is based on qualitative research, in which the participant modality was chosen. To this end, in addition to bibliographic research, data collection was performed through instruments of pedagogical practice observation; observation of pedagogical practice when teaching about the city of Cuiabá, narratives of daily spatial practices, collectice interview and didactic sequence. For data analysis, content analysis and discourse analysis were uses as reference. In daily spatial practices, concerns the displacement of the individuals to the realization of human life, based on the space-time articulation, establishing relationships with the dwelling in the city, with the world of work and with the activities of private life. It was found that daily spatial practices constitute the practical/empirical dimension of teaching geographic knowledge insofar as perception and representation are dialectical pairs in the transformation of practical/empirical knowledge into geographic/scientific knowledge. Thus, the weightings of this research show an effort to expand the understanding of wisdom derived from the practice formulated by Shulman (2014). It is also noteworthy that daily spatial practices are important references for didactic referrals in pedagogical practice in the teaching of Geography.